2023
DOI: 10.1108/tr-01-2023-0017
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and sub-orbital space tourism: motivation, constraint and artificial intelligence

Abstract: Purpose There is limited research on the behavior of different categories of space tourists as identified by different types of space tourism. To address this deficiency, the purpose of this study is to examine what factors make consumers participate in orbital and/or suborbital space tourism, along with three dimensions of motivation, constraint and artificial intelligence. To achieve this study’s goals, a comprehensive research model was developed that included three dimensions of intrinsic and extrinsic mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…M. J. Kim, Hall, Kwon, Hwang, and Kim (2023) found that extrinsic motivation and trust in AI significantly boost consumers' intentions to participate in both orbital and suborbital space tourism, while intrapersonal constraints negatively affect these intentions, highlighting distinct differences between the two forms of space tourism. According to an Extended Model of Goal-Directed Behavior for space tourism, individual interventions had a significant effect on all model constructs, but organizational interventions exert a partial impact, thereby influencing behavioral intention differently depending on experience levels (M. J.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…M. J. Kim, Hall, Kwon, Hwang, and Kim (2023) found that extrinsic motivation and trust in AI significantly boost consumers' intentions to participate in both orbital and suborbital space tourism, while intrapersonal constraints negatively affect these intentions, highlighting distinct differences between the two forms of space tourism. According to an Extended Model of Goal-Directed Behavior for space tourism, individual interventions had a significant effect on all model constructs, but organizational interventions exert a partial impact, thereby influencing behavioral intention differently depending on experience levels (M. J.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, researchers have examined consumer behavior in relation to different types of space tourism (M. J. Kim, Hall, Kwon, Hwang, & Kim, 2023; M. J. Kim, Hall, Kwon, Sohn, & Kim, 2023;Mehran et al, 2023;Paladini & Saha, 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Search engines (Carvalho and Ivanov, 2024) and social media (Azevedo, 2021) are two of the most important information sources for making such judgements. The pervasiveness and powerful computational capability of mobile technology (O’Connor, 2023), when combined with AI algorithms on the basis of tourists’ behavioural characteristics (Li et al ., 2021), make it possible for tourists to easily access information (Gonzalez et al ., 2020), book online services or even make impromptu purchases (Kim et al ., 2024).…”
Section: Innovative Technologies Reshaping Business Strategiesmentioning
confidence: 99%